Pelatihan Pembuatan dan Penggunaan E-Modul Perbankan Syariah sebagai Upaya Meningkatkan Kualitas Pembelajaran di Era Pandemi - Amirul Arif; Luqman Hakim; Susanti Susanti; Moh. Danang Bahtiar (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Education in the 21st century demands the use of technology to make innovations in the learning process, this results in social changes in the scope of education. In addition to the demands of the 21st century, the Covid-19 pandemic situation requires educators and students to be adaptive in the technology-based learning process. One of the successes in the learning process is the teaching materials used by educators. Problems that arise with partners (East Java Sharia Banking MGMP Teachers) are teaching materials that are less complex in learning, so far partners only use teaching materials in the form of printed teaching materials and pieces of each chapter of material uploaded in google classroom. Therefore, the PKM team wants to provide training to teachers who are members of the East Java Province Sharia Banking MGMP for the use and development of teaching materials. The teaching materials used in this training are e-modules assisted by the Flip PDF Professional application. The method of implementing this training activity is carried out in three stages, namely: needs analysis, implementation of training activities and evaluation of activities. The results of the questionnaire show that respondents are very interested in the training activities carried out and this activity is very useful for participants to be able to compile teaching materials in the form of E-Modules which can later be used in online learning. Keywords: Covid-19 pandemic; E-modules; Islamic banking; Online learning